A Rare Cause of a Rare Disorder: E. coli-Induced Purpura Fulminans Secondary to Urinary Tract Infection - Jacob Lowry; Edva Noel (Case Reports in Critical Care)
Purpura fulminans is a devastating thrombotic disorder infrequently encountered in medical practice and amongst the medical literature. It is a hematologic emergency in which prompt recognition and initiation of treatment are critical to mitigate its significant morbidity and mortality. Surgical evaluation is commonly required, since the debilitating skin and soft tissue necrosis often degenerate into necrotizing fasciitis, critical limb ischemia, warranting surgical interventions in either a staged or single-step approach. Purpura fulminans can be neonatal, infectious, or idiopathic. Infection-induced purpura fulminans is less common, and only a few microorganisms have been associated with this condition: Meningococcus spp., Pneumococcus spp., or Staphylococcus spp. This report presents a rare case of Escherichia coli-induced purpura fulminans. Apart from the unfortunate partial amputation of all left-hand five digits, our patient made a full recovery following effective infectious source control, supportive care with volume resuscitation, anticoagulation, and wound care.